Lyckans administration - Götselius, Thomas (K&K - Kultur og Klasse, 2016)
This article engages in the new concept of individual happiness that spread in the 18th Century and in Goethe’s pivotal novel Wilhelm Meisters Lehrjahre (1795–96). In this novel, the process of “Bildung” is designed to lead the protagonist to happiness, but happiness turns out to be possible only if the process can be governed from the outside, by powers alien to the subject. For this reason, the article argues that the notion of happiness orchestrated in the novel is not based on a revolutionary concept of happiness or a victorious Enlightenment critique, but on a concept derived from a more local field of knowledge, namely “Polizeywissenschaft”. Central to German state reform, and the practices of local administration in the late 18th Century, “Polizeywissenschaft” was developed in order to render happiness to both states and individuals, and it did so by means of surveillance and secret intervention in everyday life. On a theoretical level, the breakthrough of ”the police” during the century could be mapped as an outcome of the transition from a sovereign power regime to a biopolitical one, in Michel Foucault’s teminology. In Wilhelm Meisters Lehrjahre, as in the biopolitics encoded in the “Polizeywissenschaft,” the experience of happiness is thus coupled with a new way of governing life as such.